2023
DOI: 10.3390/biomedicines11030899
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ultra-Low Tidal Volume Ventilation during Cardiopulmonary Resuscitation on Renal and Hepatic End-Organ Damage in a Porcine Model

Abstract: The optimal ventilation strategy during cardiopulmonary resuscitation (CPR) has eluded scientists for years. This porcine study aims to validate the hypothesis that ultra-low tidal volume ventilation (tidal volume 2–3 mL kg−1; ULTVV) minimizes renal and hepatic end-organ damage when compared to standard intermittent positive pressure ventilation (tidal volume 8–10 mL kg−1; IPPV) during CPR. After induced ventricular fibrillation, the animals were ventilated using an established CPR protocol. Upon return of spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Ruemmler et al [3] were able to demonstrate in a pilot study in a porcine model that this ventilation mode, which is already well-established in acute respiratory distress syndrome (ARDS) studies [4][5][6], showed advantages in terms of brain end-organ damage and did not exhibit any disadvantages regarding oxygenation during resuscitation and up to 6 h thereafter. Similarly, another animal study by this research group showed a reduced creatinine clearance during the short-term period after return of spontaneous circulation (ROSC) applying IPPV [7], suggesting potential end-organ damage mitigation by applying ULTVV. From a physiological point of view, the use of lower tidal volumes during mechanical ventilation is associated with a decrease in intrathoracic pressure [8].…”
Section: Introductionmentioning
confidence: 72%
“…Ruemmler et al [3] were able to demonstrate in a pilot study in a porcine model that this ventilation mode, which is already well-established in acute respiratory distress syndrome (ARDS) studies [4][5][6], showed advantages in terms of brain end-organ damage and did not exhibit any disadvantages regarding oxygenation during resuscitation and up to 6 h thereafter. Similarly, another animal study by this research group showed a reduced creatinine clearance during the short-term period after return of spontaneous circulation (ROSC) applying IPPV [7], suggesting potential end-organ damage mitigation by applying ULTVV. From a physiological point of view, the use of lower tidal volumes during mechanical ventilation is associated with a decrease in intrathoracic pressure [8].…”
Section: Introductionmentioning
confidence: 72%